Оцінка інвестиційної привабливості фінансових інструментов у сучасних нестійких економічних умовах - Стеценко, С. П. (Ways to Improve Construction Efficiency, 2012)
The article discussed and investigated methodological aspects of evaluation of investment shares in the current unstable economic conditions. A comparative analysis of the attractiveness of the shares of public companies of the energy sector, listed on the domestic stock market. To make effective investment decisions on the purchase and sale of securities identified undervalued companies and investment attractive stocks.